The rise of populist nationalism : social resentments and the anti-constitutionalist turn in Hungary - Feischmidt, Margit; Majtényi, Balázs (Central European University Press, 2019)
"The authors of this book approach the emergence and endurance of the populist nationalism in post-socialist Eastern Europe, with special emphasis on Hungary. They aim to understand the reasons behind the growing public discourses that seek to reframe politics in terms of nationhood and nationalism. The contributors focus on two motifs in public discourse: shift and legacy. Each offers answers to important theoretical questions endemic to Eastern Europe by combining empirical and normative social science perspectives. Some contributors focus on shifts in public law and shifts in political ethno-nationalism through the lens of constitutional law, while others explain the social and political causes of those shifts. The authors also discuss the effects of legacy in memory and culture but suggest that both shift and legacy are intertwined in producing the new era of identity politics. Overall, this volume attempts to explain how new nationalism is rooted in recent political, economic and social processes. The legal experts in the volume emphasize that the new Fundamental Law of Hungary is radically different from all previous Hungarian constitutions, and is a quasi-mirror for how the identity of the Hungarian state itself is being redefined. The book further examines the role of certain structural processes within sociology and political science in strengthening identity politics"--